Situating English Language Teaching in India within the Framework of Post Method Pedagogy - Malik , Masood Ahmad (International Journal of Psychosocial Rehabilitation, 2020)
The horizontal expansion and vertical percolation of English language in India has been uneven primarily because of the lack of concerted efforts by the different stake holders. One of the main reasons has been the unfiltered imposition of Anglo American or Eurocentric teaching methods for the teaching of English which have failed to produce the desired results. The use of imported methods has not only sidelined the teachers but has also taken the whole teaching learning process as its hostage. Consequently unlike urban areas where due to the exposure to media and social networking, students are relatively proficient in the use of English, the students of the rural and tribal areas in India are having a very low proficiency in English which becomes a main cause of their exclusion from the higher education and the job market. The marginalization of the indigenous educational traditions and practices and promotion of the western educational traditions without any scrutiny has put the teaching and learning of English in India at the cross roads. The University Grants Commission of India in its Learning Outcome based Curriculum Framework (LOCF) of English also advocates use of local resources and teacher innovation for the teaching of English in India.  Keeping the unproductive use of method oriented pedagogy in India  and the recommendations of LOCF in mind, the present paper builds a case for using Post Method pedagogy which unlike the so called methods is a bottom up approach and is based on the experiential knowledge of the practicing  teachers and takes the local social, cultural , administrative and educational exigencies into consideration.